2019
DOI: 10.1136/heartjnl-2019-314817
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal outcomes in pregnancies complicated by Marfan syndrome

Abstract: ObjectivesInformation to guide counselling and management for pregnancy in women with Marfan syndrome (MFS) is limited. We therefore conducted a UK multicentre study.MethodsRetrospective observational study of women with MFS delivering between January 1998 and March 2018 in 12 UK centres reporting data on maternal and neonatal outcomes.ResultsIn total, there were 258 pregnancies in 151 women with MFS (19 women had prior aortic root replacements), including 226 pregnancies ≥24 weeks (two sets of twins), 20 misc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 26 publications
2
42
2
Order By: Relevance
“…Similar to the findings of Cauldwell et al (2019), we reported no maternal deaths. Other studies on MFS and pregnancy have found higher risk of adverse cardiovascular events, particularly aortic dissection (Cauldwell et al, 2019; Curry et al, 2014), accelerated aortic dilation, and progressive aortic and mitral regurgitation (Donnelly, Pinto, Kocolas, & Yetman, 2012; Meijboom et al, 2005; Rossiter, Repke, Morales, Murphy, & Pyeritz, 1995). However, in our study, no adverse cardiovascular events occurred in women with MFS.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the findings of Cauldwell et al (2019), we reported no maternal deaths. Other studies on MFS and pregnancy have found higher risk of adverse cardiovascular events, particularly aortic dissection (Cauldwell et al, 2019; Curry et al, 2014), accelerated aortic dilation, and progressive aortic and mitral regurgitation (Donnelly, Pinto, Kocolas, & Yetman, 2012; Meijboom et al, 2005; Rossiter, Repke, Morales, Murphy, & Pyeritz, 1995). However, in our study, no adverse cardiovascular events occurred in women with MFS.…”
Section: Discussionsupporting
confidence: 92%
“…One patient in early gestation (12 weeks) was recommended termination of pregnancy; she had MFS and a prior AVR. No information was available on this case, but she went on to have medical treatment only 59 . This supports the consensus of delivering where possible and subject to fetal viability.…”
Section: Reviewsupporting
confidence: 53%
“…A recent study comprising of 12 UK centers, over the past 20 years shows that the rate of aortic dissection in pregnant women with MFS was 1.9% (one type A and four type B) and there were no deaths. It also reports that preconception counseling rates were low [4]. The patient in our case did not undergo pre-conception counseling.…”
Section: Discussionmentioning
confidence: 53%